The Effectiveness of Using Gadgets on Students’ Learning Interests and Academic Performance - Madarcos, Cherry Ann; De Vera, Mercy Grace; Manlavi, Maribeth (Yayasan Nurul Yakin Bunga Tanjung, 2024)
This quantitative study contributes to the literature by focusing on the increasing prevalence of technology in everyday life and the growing use of gadgets in educational settings. It aimed to evaluate the impact of gadgets on the student’s academic performance at Paly National High School in Taytay, Palawan. A survey was conducted among 145 students from grade 7 to grade 10 who were chosen to participate in this study through stratified random sampling. The data was analyzed using SPSS software, and inferential statistics, correlation, and independent t-tests were used to identify relationships between academic performance and gadget use. Descriptive statistics were used to interpret the quantitative data on students’ perceptions of gadget use and its impact on academic performance. The study revealed no significant difference in the mean scores among respondents with different gadgets, including desktops, laptops, mobile phones, and iPads. Similarly, findings also implied that specific purposes for which respondents used gadgets did not influence their academic performance. However, most of the respondents overwhelmingly disagree that gadget use has detrimental effects, indicating that the beneficial influence of gadgets on academic achievement outweighs potential drawbacks. Educators may explore ways to integrate technology into the curriculum effectively.